2020
DOI: 10.21203/rs.2.16834/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Diabetes Mellitus on short-term prognosis of 227 pyogenic liver abscess patients after hospitalization

Abstract: Background: Pyogenic liver abscess (PLA) is an inflammatory disease with increasing incidence. When it occurs with diabetes mellitus (DM), risk of recurrence and the mortality may increase. However, the effect of DM on short-term prognosis of PLA patients after hospitalization remained unknown. Methods: 227 PLA patients who received treatment at the First Affiliated Hospital of Xi’an Jiaotong University from January 2011 to January 2018 were retrospectively enrolled. They were divided into two groups as DM gro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…The overall median age of our patients was 68 years, which is higher than that of other reported large series that showed a mean age between 52 and 62 years [1,15,[24][25][26][27].…”
Section: Discussioncontrasting
confidence: 66%
“…The overall median age of our patients was 68 years, which is higher than that of other reported large series that showed a mean age between 52 and 62 years [1,15,[24][25][26][27].…”
Section: Discussioncontrasting
confidence: 66%
“…Although less influential than cancer, diabetes showed a significant effect on in‐hospital mortality. Similarly, previous studies have reported cancer and diabetes as risk factors for PLA mortality 40‐45 …”
Section: Discussionmentioning
confidence: 70%
“…All current data show that without doubt good therapy of all risk factors, such as diabetes mellitus, is crucial for the prognosis of the disease. [19][20][21][22] This also applies to the case described here. However, the optimal therapy for diabetes mellitus can only be achieved through the cooperation of the patient and the close supervision by the GP s. This is also possible via telemedical offers.…”
Section: Discussionmentioning
confidence: 70%